Doing your education research project - Burton, Neil, 1960-; Brundrett, Mark; Jones, Marion (Professor of teacher education) (Los Angeles : Sage, 2014)
A practical guide offering simple steps for trainee teachers or experienced practitioners new to research, on getting started with their education research project.
Think before you do-planning -- Gathering your evidence -- Making sense of the outcomes.
Previous edition: 2008.
Includes bibliographical references and index.
Text in English.
Self-Renewing
Keywords: Education -- Research -- Methodology; Education -- Research -- Methodology